Design and Optimization of High-Speed Optical Fiber Networks for 5G and Beyond - Deepak Prajapati, Dr. Ritesh Baranwal, Ravi Prakash (Cuestiones de Fisioterapia, 2025)
The deployment of 5G and future communication networks necessitates an advanced infrastructure capable of supporting unprecedented data rates, low latency, and high connectivity. High-speed optical fiber networks play a critical role in this transformation, providing the necessary bandwidth and reliability to handle the complex demands of 5G applications such as the Internet of Things (IoT), enhanced mobile broadband, and ultra-reliable low-latency communications.